Pemanfaatan Artificial Intelligence pada Pembelajaran Bahasa Indonesia di Sekolah Dasar : Analisis Bibliometrik - Welly Firdaus (LPPM STAI Muhammadiyah Probolinggo, 2026)
The development of digital technology has brought significant changes to the world of education, including in the teaching of Indonesian in elementary schools. One of the increasingly emerging innovations is the use of artificial intelligence (AI) as a learning support. AI enables the learning process to be more interactive, adaptive, and tailored to the needs of students, thus functioning not only as an aid but also as an innovative solution to improve the quality of learning. This study aims to analyze research trends related to the use of AI in elementary school education, specifically Indonesian language learning, using a bibliometric approach. This method is used to systematically examine the patterns, distribution, and development of scientific publications. The research data includes 1,006 documents from the Dimensions.ai database from 2021–2025, which have been selected for relevance. The analysis results show a significant increase in the number of publications since 2021 and peaked in 2024. The most dominant fields include education, philosophy, and religious studies, indicating that AI studies focus not only on technology but also on ethical and value aspects. These findings are expected to serve as a reference for educators and policymakers in developing the use of AI to improve the quality of learning in elementary schools sustainably.